Wall Works : Architekturbezogene Wandarbeiten - Flavin, Dan; Paula Cooper Gallery, New York; Edition Schellmann, New York; Museum Villa Stuck, München; Edition Schellmann, München (München : Schirmer/Mosel, 1999)
Artschwager, Richard ; Buren, Daniel ; Diamond, Jessica ; Riverhead (New York) ; Fleury, Sylvie ; Förg, Gunther ; Gilbert & George ; Grünfeld, Thomas ; Halley, Peter ; Hirst, Damien ; Judd, Donald ; Knoebel, Imi ; Kosuth, Joseph ; Kounellis, Jannis ; Levine, Sherrie ; LeWitt, Sol ; Merz, Gerhard ; Mullican, Matt ; Oursler, Tony ; Paik, Nam June ; Paolini, Giulio ; Pistoletto, Michelangelo ; Schnabel, Julian ; Sherman, Cindy ; Steinbach, Haim ; Stingel, Rudolf ; Trockel, Rosemarie ; Walker, Kara ; Warhol, Andy
biografie
Duits & Engels
Wall Works - a group of 38 wall installations, Paul Cooper Gallery, New York, February 20 - March 20 1999 ; Edition Schellmann, New York, February 20 - April 20 1999 ; Museum Villa Stuck, München, September - November 1999 ; Edition Schellmann, München, September - November 1999
boek